The Influence of Spatial Urbanization to Regional Condition in Periurban Areas of Yogyakarta - Kurniawan, Andri; Prakoso, Bambang Sriyanto Eko (Universitas Muhammadiyah Surakarta, 2008)
It is interesting to study periurban areas because of its transitional characteristic. Periurban areas undergo dynamic changes as a result of spatial urbanization. This study is aimed at: (1) examining the development pattern of spatial urbanization in Yogyakarta and finding out the influential determinant factors; (2) examining the dynamics of land use changes in periurban areas and finding out the resultant impacts; (3) examining the pattern and development of services (infrastructures) and finding out the determinant factors supporting the development of services (infrastructures) in periurban areas; (4) examining the role of the development of periurban services (infrastructures) as magnetic forces for periurban development; and (5) making policies concerning periurban development and management in order to achieve optimal development and to balance the functions of urban and rural areas. The methods used in this research are secondary data analyses and aerial photo interpretation. This study applies secondary data analysis by comparing the data to find out the extent of the changes. Descriptive statistics, scaling, and discri-minant analysis are used as the analytical techniques to find out the determinant factors of urban growth in periurban areas. Spatially, urbanization in Yogyakarta periurban areas tends to move toward the western part (Ngestiharjo village), northern part (Catur Tunggal village) and eastern part (Banguntapan village). Besides centrifugal forces, the development of built land and urban characteristics in the western, northern and eastern parts are also influenced by the main roads (corridors) from Yogyakarta to Kaliurang, from Yogyakarta to Wates, and from Yogyakarta to Solo. The existence of the corridors prompts the functions of trade and services which, in turn, trigger the development of the surrounding housing complex. On the contrary, in the southern and south-east part of Yogyakarta the activities of service have not yet well-developed and neither have the new housing complex. The development of number and density population are variables determining urban development in Yogyakarta periurban areas. The dynamics of land use changes in Yogyakarta periurban areas are characterized by the decrease in agricultural land (6.46 % per year) and the increase in built land. The decrease in agricultural land reduces the sustainability of agricultural environment. Agricultural production can no longer satisfy periurban peopleâs needs for food. The different strength in interaction results in the difference in the facilities of service (infrastructure) between periurban areas. The periurban dynamics in Yogyakarta are also characterized by the increase in function and sustainability of services. The development of service (infrastructure) in Yogyakarta periurban areas have a lot of impacts especially those related to the increase in urban characteristics. In some parts of periurban areas, there is a relation between the increase in service provision and the development of urban characteristics.